2021
DOI: 10.3390/cancers13164029
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Genomics, Transcriptomics, and Epigenomics to Understand the Biology and Chemoresistance of Ovarian Cancer

Abstract: Ovarian cancer is a major cause of fatality due to a gynecological malignancy. This lethality is largely due to the unspecific clinical manifestations of ovarian cancer, which lead to late detection and to high resistance to conventional therapies based on platinum. In recent years, we have advanced our understanding of the mechanisms provoking tumor relapse, and the advent of so-called omics technologies has provided exceptional tools to evaluate molecular mechanisms leading to therapy resistance in ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…These heterocellular aggregate structures are designated “metastatic units” because of their unique contributions to tumor spread within the peritoneal cavity and construction of the metastatic niche [ 86 ]. Indeed, recent transcriptomic, epigenomic, mass spectroscopy, spatial transcriptomic and multiplexed imaging approaches, at both the bulk tumor and single-cell levels, clarified the complexity of the cellular interactions in the ovarian tumor microenvironment underlying development of resistance to chemotherapy (e.g., [ 93 , 94 , 95 ]).…”
Section: Heterotypic Spheroids: a Specialized Caf–tumor Microenvironmentmentioning
confidence: 99%
“…These heterocellular aggregate structures are designated “metastatic units” because of their unique contributions to tumor spread within the peritoneal cavity and construction of the metastatic niche [ 86 ]. Indeed, recent transcriptomic, epigenomic, mass spectroscopy, spatial transcriptomic and multiplexed imaging approaches, at both the bulk tumor and single-cell levels, clarified the complexity of the cellular interactions in the ovarian tumor microenvironment underlying development of resistance to chemotherapy (e.g., [ 93 , 94 , 95 ]).…”
Section: Heterotypic Spheroids: a Specialized Caf–tumor Microenvironmentmentioning
confidence: 99%
“…Thus, a combination treatment of pGSN inhibition and ICI could considerably enhance OVCA patient outcomes. Epigenetic alterations, including DNA methylation and histone modifications, cause chemotherapy resistance in ovarian cancer [ 111 ]. DNA methyltransferase 1 and histone deacetylase are involved in epigenetic alteration [ 112 , 113 ].…”
Section: Summary and Future Research Directionsmentioning
confidence: 99%
“…However, existing studies have found that the pathogenesis of OCCC is similar to endometrial cancer, such as inactivation of tumor suppressor genes such as PTEN (phosphatase and tensin homologue) and ARID1A (AT-rich interactive domain 1A), activation of the PI3K/AKT/mTOR (phosphoinositide-3 kinase/protein kinase-B/mammalian) signal pathway, and high microsatellite instability (MSI) ( Ueda et al, 2005 ; Gounaris et al, 2011 ; Xiao et al, 2012 ; Worley et al, 2015 ; Willis et al, 2017 ). With the development of next-generation sequencing, our knowledge about tumorigenesis and the mechanisms of tumor cell proliferation, immune avoidance and antitumor therapy has increased ( Munoz-Galvan and Carnero, 2021 ). In this review, we summarized recent advances in the molecular characteristics of OCCC from the perspective of genomics and epigenomics ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%